Modal Kerja Dan Struktur Modal Dalam Memprediksi Profitabilitas Perusahaan Sektor Barang Konsumsi - Jessi Amelia, Nyoman Suprastha (Jurnal Manajerial Dan Kewirausahaan, 2019)
Profitability is one indicator that determines a company's ability to maintain continuity and carry out growth. There is no consensus regarding the factors that determine the profitability of the company. This study examines the factors that influence profitability, such as working capital and capital structure. The purpose of this study is to conduct empirical research using panel data regression methods to determine company-specific factors that affect profitability. This study uses a sample of 27 companies, which are listed on the Indonesia’s Stock Exchange (IDX) for the period 2013-2017. It was concluded that the capital structure cannot predict the company's profitability significantly. While working capital can predict a significant profitability of the company